'A preferred consultant and partner to the Royal Government, NGOs, and the community': British American Tobacco's access to policy-makers in Cambodia. Issue 4 (3rd April 2017) - MacKenzie, Ross; Collin, Jeff
ABSTRACT: British American Tobacco Cambodia (BATC) has dominated the country's tobacco market since its launch in 1996. Aggressive marketing in a weak regulatory environment and strategies to influence tobacco control policy have contributed to an emerging tobacco-related public health crisis. Analysis of internal tobacco industry documents, issues of BATC's in-house newsletter, civil society reports and media demonstrate that BATC officials have successfully sought to align the company with Cambodia's increasingly controversial political and business leadership that is centred around the Cambodian People's Party with the aim of gaining access to policy-makers and influencing the policy process. Connections to the political elite have resulted in official recognition of the company's ostensible contribution to Cambodia's economic and social development and, more significantly, provided BATC with opportunities to petition policy-makers and to dilute tobacco control regulation. Corporate promotion of its contribution to Cambodia's economic and social development is at odds with its determined efforts to thwart public health regulation and Cambodia's compliance with the Framework Convention on Tobacco Control.